2003
DOI: 10.1007/s00253-003-1291-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro reduction of hexavalent chromium by a cell-free extract of Bacillus sp. ES 29 stimulated by Cu 2+

Abstract: Chromium-resistant bacteria (CRB) isolated from soils can be used to reduce toxic Cr(VI) from contaminated environments. This study assessed in vitro reduction of hexavalent Cr using a cell-free extract (CFE) of CRB isolated from soil contaminated with dichromate. One isolate, ES 29, that substantially reduced Cr(VI) was identified as a Bacillus species by 16S rRNA gene-sequence homology. The isolate reduced Cr(VI) under aerobic conditions, using NADH as an electron donor and produced a soluble Cr(VI)-reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 17 publications
7
106
2
1
Order By: Relevance
“…We therefore presume that chromate reductase is a membrane-bound enzyme in both isolates and is also secreted in the extracellular environment. Camargo et al [13] observed chromate reductase activity in the cell-free extract and soluble fraction but very low activity in the membrane fraction of Bacillus sp. ES29.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore presume that chromate reductase is a membrane-bound enzyme in both isolates and is also secreted in the extracellular environment. Camargo et al [13] observed chromate reductase activity in the cell-free extract and soluble fraction but very low activity in the membrane fraction of Bacillus sp. ES29.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Bacillus Sp. ES29 reduced 90% of Cr(VI) added (2 mg/l) to the medium in less than 6 h [13]. Thacker and Madamwar [14] have shown that the bacterial isolate DM1 reduces 50 ppm of chromium to 0 ppm in 54 h. They added a second aliquot of chromium which was reduced to 0 ppm in 99 h, and the third aliquot was reduced to 21.8 ppm in 126 h.…”
Section: Resultsmentioning
confidence: 99%
“…Park et al [13] had demonstrated that Pseudomonas putida culture was able to carry out enzymatic reduction of chromates. Cr(VI) was also shown to be quantitatively transformed to Cr(III) largely by soluble reductase activities in Bacillus species isolated from chromium-contaminated soil samples [5] Chromium reduction by the Bacillus species was not affected by sulphate and/or nitrate. The removal of chromium ions by the cyanobacterium, Anacystis nidulans immobilised on agar has been documented [3] Reports on chromate reduction by resting cells of sulphate-reducing bacteria particularly, Desulfovibrio vulgaris [17] and Cellulomonas sp.…”
Section: Introductionmentioning
confidence: 92%
“…Many species of bacteria [1,[3][4][5][6][7][8], yeasts [9][10][11] and fungi [12][13][14][15][16] have been investigated from this aspect, and the biosorption and bioaccumulation of chromium for bioremediation purposes have been demonstrated. Park et al [13] had demonstrated that Pseudomonas putida culture was able to carry out enzymatic reduction of chromates.…”
Section: Introductionmentioning
confidence: 99%
“…However, a hyper-resistant Bacillus sp. ES29 has been reported who is resistant to very high level of Cr (VI) at > 9.6 mM (Camargo et al, 2003b). In our experiments, higher Cr (VI) concentration (3.4 mM) caused decrease in growth rate when compared to growth at lower concentrations; this was ascribed to the toxic effect of Cr (VI).…”
Section: Discussionmentioning
confidence: 46%